Upper river basin watersheds: sustainable, equitable and profitable interventions - CGIAR Research Program on Water, Land and Ecosystems (International Water Management Institute, 2018)
The CGIAR Research Program on Water, Land and Ecosystems (WLE) has conducted innovative research in the upper watersheds of the Ganges, Mekong, Red and Nile river basins. WLE sought to identify how to improve people’s livelihoods in ways that are equitable, profitable and sustainable, while also improving ecosystem services locally and downstream. The research specifically examined the impact of interventions spanning several sectors, including water, food, energy and trade. This brief presents results, insights and tools that can be adopted and applied elsewhere. Escaping from the confines of narrow sectoral investments and adopting an integrated, ecosystems-focused approach can lead to more sustainable, profitable and equitable use and development of upper watershed landscapes.